PENGGUNAAN WEARABLE INTERNET OF THINGS (WIoT) OLEH KAUM MILENIAL - Dian Lorinsa (Universitas Teuku Umar, 2020)
In digital era like now, internet and millennial generation are inseparable, the use of the internet of things adopted into wearable devices such as Applewatch products is very interesting to explore. This article tries to analyze the extent of the use of the internet of things for Applewatch users in Indonesia, especially among millennial generation. This research article uses a meta-analysis method that reveals previous research related to the concept and object of research, which is complemented by observations and interviews with individuals belonging to millennials, namely those born between 1980-2000. The results of 18 previous research articles related to research on the internet of things, wearable devices in the millennial generation, have not found research that focuses on the use of wearable devices in this case Applewatch. The results of interviews with millennial samples of Applewatch users in Indonesia found that the use of Applewatch is primarily as an alternative and complement to smartphones and is used for notification and wearable fast response tools. Applewatch users have not utilized the technology and health features available to the full.